Diphenhydramine as a Cause of Drug-Induced Liver Injury - Yunseok Namn; Yecheskel Schneider; Isabelle H. Cui; Arun Jesudian (Case Reports in Hepatology)
Drug-induced liver injury (DILI) is the most common cause of acute liver failure in the Unites States and accounts for 10% of acute hepatitis cases. We report the only known case of diphenhydramine-induced acute liver injury in the absence of concomitant medications. A 28-year-old man with history of 13/14-chromosomal translocation presented with fevers, vomiting, and jaundice. Aspartate-aminotransferase and alanine-aminotransferase levels peaked above 20,000 IU/L and 5,000 IU/L, respectively. He developed coagulopathy but without altered mental status. Patient reported taking up to 400 mg diphenhydramine nightly, without concomitant acetaminophen, for insomnia. He denied taking other medications, supplements, antibiotics, and herbals. A thorough workup of liver injury ruled out viral hepatitis (including A, B, C, and E), autoimmune, toxic, ischemic, and metabolic etiologies including Wilson’s disease. A liver biopsy was consistent with DILI without evidence of iron or copper deposition. Diphenhydramine was determined to be the likely culprit. This is the first reported case of diphenhydramine-induced liver injury without concomitant use of acetaminophen.